2020
DOI: 10.3390/biom10101440
|View full text |Cite
|
Sign up to set email alerts
|

Erinacine C Activates Transcription from a Consensus ETS DNA Binding Site in Astrocytic Cells in Addition to NGF Induction

Abstract: Medicinal mushrooms of the genus Hericium are known to produce secondary metabolites with homeostatic properties for the central nervous system. We and others have recently demonstrated that among these metabolites cyathane diterpenoids and in particular erinacine C possess potent neurotrophin inducing properties in astrocytic cells. Yet, the signaling events downstream of erinacine C induced neurotrophin acitivity in neural-like adrenal phaeochromocytoma cells (PC12) cells have remained elusive. Similar, sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 33 publications
1
17
0
Order By: Relevance
“…According to [23], cyathane diterpenes isolated from the submerged cultures of H. erinaceus and H. flagellum were found to act on 1321N1 cells by increasing the transcription of either bdnf or ngf . Similarly, a study by [11] reported that erinacine C influenced the expression in these astrocytic cells on the transcriptional level, probably including also factors that regulate ngf expression. In the present study, we clearly demonstrated that the triterpenoids increases ngf and bdnf synthesis in 1321N1 cells.…”
Section: Resultsmentioning
confidence: 78%
See 4 more Smart Citations
“…According to [23], cyathane diterpenes isolated from the submerged cultures of H. erinaceus and H. flagellum were found to act on 1321N1 cells by increasing the transcription of either bdnf or ngf . Similarly, a study by [11] reported that erinacine C influenced the expression in these astrocytic cells on the transcriptional level, probably including also factors that regulate ngf expression. In the present study, we clearly demonstrated that the triterpenoids increases ngf and bdnf synthesis in 1321N1 cells.…”
Section: Resultsmentioning
confidence: 78%
“…As control, serum-reduced medium supplemented with 0.5% DMSO was used. Cells were incubated for 48 h [11,23]. Total RNA was extracted using the NucleoSpin R RNA Plus kit (Macherey-Nagel GmbH& Co KG, Germany) followed by further purification (NucleoSpin R RNA Clean-up kit) according to the manufacturer’s protocol.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations